Expectations of postgraduate nursing students: an inquiry - S Lekalakala-Mokgele (AOSIS, 2008)
Postgraduate supervision in South Africa currently takes place in the context of university transformation with a notable increase in concern for quality. The latter is determined by the extent to which students' expectations within a supervisory practice are met. This study investigated students' expectations regarding their research supervision in a postgraduate nursing programme. A 48-item questionnaire was mailed to 24 postgraduate students, of which 22 (92%) responded, to determine their expectations within a supervisory relationship. Items in the questionnaire included students' perceptions of the responsibilities of the institution, the department, the supervisor and students' responsibilities regarding their supervised postgraduate studies in the School of Nursing Science. Descriptive statistics, namely frequencies and percentages for categorical data and means and standard deviations or medians and percentiles for continuous data, were calculated. Findings indicate that more than 80% of the postgraduate students in the study expected the university and the department to provide them with structures that would enable them to succeed in their studies. They also believed that the student had a major role to play in ensuring that studies were completed. Recommendations included making a code of practice for postgraduate supervision available to students and the use of a learning contract to clarify roles and expectations in the supervisory process. It was also recommended that supervisors should be trained to supervise students.